The Role of Autophagy in Salivary Gland Homeostasis and Stress Responses. (August 2015) - Morgan-Bathke, M.; Lin, H.H.; Ann, D.K.; Limesand, K.H.
Autophagy is a catabolic process that has been shown to have a role in many cellular processes including the removal of excessive or damaged proteins and protein aggregates. The salivary glands play a critical role in oral health, and their secretory capacity may be critically intertwined with the autophagic process. This review describes the role of autophagy activation in normal salivary gland homeostasis and during the glandular stress responses of therapeutic radiation, ductal ligation, autoimmunity, and salivary gland adenoid cystic carcinoma.